To Unfold the Immigrant Paradox: Maltreatment Risk and Mental Health of Racial-Ethnic Minority Children - Zhang, Liwei; Bo, Ai; Lu, Wenhua (Frontiers in Public Health, 2021)
Children of immigrants are often considered to be at increased risk of mental health problems due to families' immigration-related stress and perceived discrimination and prejudice from the host country. However, many studies found them to have better developmental outcomes than children with native-born parents in the U.S. This study aims to unfold this paradoxical phenomenon using data from a population-based cohort of children born in large U.S. cities. Specifically, we investigated differences in mental health outcomes between children of immigrants and those with native-born parents, stratified by children's race-ethnicity. We also explored the mediating role of child maltreatment risk in the association of parental nativity status and race-ethnicity with children's mental health. Our findings supported the immigrant paradox, with better self-reported and parent-reported internalizing and externalizing outcomes in Hispanic and Black children of immigrants than their same race-ethnicity peers and White children of native-born. Such immigrant-native variations were partially explained by parents' physically and psychologically abusive behaviors. Hispanic and Black children with immigrant parents were less likely to be physically or psychologically abused than their peers of native-born at ages 4–5, which translated into mental health advantages of children of immigrants at age 9. Our findings shed light on future research to further clarify the mechanism underlying different parenting practices between same race-ethnicity immigrants and native-born families so that culturally responsive interventions can be developed to safeguard racial-ethnic minority children's mental health.